Selective Pyridine-Directed C–H Activation Enabled Synthesis of Pyridine-pyridone α-Helix Mimics - Xiao, Dong; Song, Zhiguo J.; Song, Zhiyan (Synlett, 2025)
The exploration of pyridine-directed C–H activation in 2-benzyl-6-phenylpyridine revealed selective bromination at the ortho-phenyl position via Rh catalysis, rather than the ortho-benzyl position. In contrast, the corresponding alkylation was unsuccessful, suggesting a preference for the Rh(III) pathway to minimize steric congestion from pyridine disubstitution. This mechanistic insight facilitated the development of a room-temperature C–H activation–bromination method, enabling the synthesis of a pyridine-pyridone α-helix mimic.
Keywords: Rh-catalyzed C–H activation; reaction mechanisms; selectivity; C–H activation; heterocycle synthesis; α-helix mimics